Technical and tactical readiness of the team "Helios" (Kharkiv) in the 26th Ukrainian soccer championship in the first league - Serhii Zhurid; Oleksandr Dovbiy (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to determine the model characteristics of the technical and tactical readiness of the team that participated in the Ukrainian championship of the first league in order to further improve and correct the training process. Material & Methods: the data were obtained using the method of expert evaluation, the calculation was carried out using the methods of mathematical statistics. Results: analyzed the average values of the registered values for 19 games. Analyzed various technical and tactical actions and their differences in the first and second halves, as well as individual indicators of the game players and the team "Helios" (Kharkiv). Conclusion: quantitative and qualitative (rejection rate) indicators were obtained both for team technical and tactical actions, and separately for each technical and tactical method for each game period.